An Update on the Discovery, Pathophysiological Actions, Clinical Manifestations and Possible Physiology of Parathyroid Related Peptide - Alcantara, Aurora; Montalvo-Figueroa, José A.; Toro, Suzette; Aguilo, Francisco (Puerto Rico Health Sciences Journal, 2025)
see manuscript